THE EFFECT OF CUPPING THERAPY ON HEMOGLOBIN LEVELS IN SMOKERS AND NON-SMOKERS - Syadza Iffat Firdauzi; Titik Kusumawinakhyu (International Journal of Islamic and Complementary Medicine, 2023)
Cupping therapy, known as bekam in Arabic and blood cupping in English, is a therapeutic practice mentioned in Islamic teachings and hadiths. It is believed to have health benefits and is recommended for healing. One hadith state: There are three remedies for healing: cupping, drinking honey, and cauterizing with fire. But I forbid my followers from cauterizing with fire (Narrated by Bukhari). Based on this hadith, cupping therapy is considered beneficial for health and treatment.  The aim of this study is determining the effect of cupping therapy on hemoglobin levels in smokers and non-smokers.  This study employed a quantitative research design with an observational approach using a one-time pretest and posttest without control group design. The research sample was obtained through simple random sampling and consisted of 30 individuals, including smokers and non-smokers. Primary data were collected directly from the cupping therapy procedure, while secondary data were obtained from physical examinations of the respondents. There is no effect of cupping therapy on hemoglobin levels in smokers and non-smokers.